Measuring emotional intelligence with the MSCEIT 2: theory, rationale, and initial findings - John D. Mayer; David R. Caruso; Peter Salovey; Iris Y. Lin; Braden J. Hansma; Joanna Solomon; Gill Sitarenios; Manolo Romero Escobar (Frontiers in Psychology)
IntroductionThe model of emotional intelligence as an ability has evolved since its introduction 35 years ago. The revised model includes that emotional intelligence (EI) is a broad intelligence within the Cattell-Horn-Carroll (CHC) model of intelligence, and that more areas of problem solving are involved than originally detailed. An argument is made here that veridical scoring of EI test responses is a sound procedure relative to scoring keys based on expert consensus or a single emotion theory. To the degree that EI fits present-day theories of intelligence (i.e., the CHC model), any subsidiary factors of EI reasoning should correlate highly with one another. These and other considerations led to a revision of the original Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) to the MSCEIT 2.MethodsThe MSCEIT 2 was developed and tested across 5 studies: Two preliminary studies concerned, first, the viability of new item sets (Study 1, N = 43) and, in Study 2 (N = 8), the development of a veridical scoring key for each test item with the assistance of Ph.D. area experts. Next, a pilot study (Study 3, N = 523) and a normative study (Study 4, N = 3,000) each focused on the test’s item performance and factor structure, including whether a four-domain model continued to fit the data in a manner consistent with a cohesive broad intelligence. Study 5 (N = 221) examined the relation between the original and revised tests.ResultsThe studies provide evidence for factor-supported subscale scores, and good reliability at the overall test level, with acceptable reliabilities for 3 of the 4 subscale scores, and adequate measurement precision across the range of most test-takers’ abilities.DiscussionOverall, the MSCEIT 2 used updated theory to guide its construction and development. Its test scores fit the CHC model, and correlate with the original MSCEIT. The revised test is 33% shorter than the original.